2019
DOI: 10.1101/627380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CENP-F controls force generation and the dynein-dependent stripping of CENP-E at kinetochores

Abstract: Accurate chromosome segregation demands efficient capture of microtubules by kinetochores and their conversion to stable bi-oriented attachments that can congress and then segregate chromosomes. An early event is the shedding of the outermost fibrous corona layer of the kinetochore following microtubule attachment. Centromere protein F (CENP-F) is part of the corona, contains two microtubule-binding domains and physically associates with dynein motor regulators. Here, we have combined CRISPR gene editing and e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…In addition to mechanical roles at the nuclear envelope and mitochondrial outer membrane in G2 [ 52 , 53 ], CENP-F is recruited to outer kinetochores through a direct interaction with Bub1 in mitosis, providing a potential Bub1-dependent pathway for CENP-E recruitment to kinetochores [ 33 , 35 , 50 , 52 ]. Individual depletion of CENP-E and CENP-F indicate they show interdependency in their kinetochore localization [ 50 , 54 , 55 ]. Yet, in nocodazole-treated cells CENP-E is retained strongly at the kinetochore in the absence of CENP-F, indicating that CENP-F is not essential for CENP-E targeting to unattached kinetochores [ 33 , 54 , 55 ].…”
Section: Mechanisms Of Cenp-e Recruitment To Kinetochoresmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to mechanical roles at the nuclear envelope and mitochondrial outer membrane in G2 [ 52 , 53 ], CENP-F is recruited to outer kinetochores through a direct interaction with Bub1 in mitosis, providing a potential Bub1-dependent pathway for CENP-E recruitment to kinetochores [ 33 , 35 , 50 , 52 ]. Individual depletion of CENP-E and CENP-F indicate they show interdependency in their kinetochore localization [ 50 , 54 , 55 ]. Yet, in nocodazole-treated cells CENP-E is retained strongly at the kinetochore in the absence of CENP-F, indicating that CENP-F is not essential for CENP-E targeting to unattached kinetochores [ 33 , 54 , 55 ].…”
Section: Mechanisms Of Cenp-e Recruitment To Kinetochoresmentioning
confidence: 99%
“…Individual depletion of CENP-E and CENP-F indicate they show interdependency in their kinetochore localization [ 50 , 54 , 55 ]. Yet, in nocodazole-treated cells CENP-E is retained strongly at the kinetochore in the absence of CENP-F, indicating that CENP-F is not essential for CENP-E targeting to unattached kinetochores [ 33 , 54 , 55 ]. Whether CENP-E and CENP-F interact at the kinetochore remains controversial and a direct interaction between CENP-E and CENP-F has yet to be reconstituted in vitro .…”
Section: Mechanisms Of Cenp-e Recruitment To Kinetochoresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, premature RZZ shedding from KTs must be avoided to allow some degree of KT-MT attachment plasticity and prevent stabilization of erroneous endon attachments that might form during early mitosis [45,47]. Similarly to a recently proposed "DYNEIN brake" mechanism to maintain CENP-E at KTs [74], it has been suggested that cells must block untimely removal of RZZ from KTs. However, the molecular underpinnings of such mechanism had never been established [61].…”
mentioning
confidence: 99%